PENANAMAN NILAI-NILAI DAKWAH KULTURAL NAHDLATUL ULAMA TERHADAP KERUKUNAN UMAT BERAGAMA DALAM PENDEKATAN HADIS/SUNNAH DI KOTA PAREPARE - JUFRI, MUHAMMAD (P3M STAIN Parepare, 2014)
The results of this study reveal about strategies and models of cultural propaganda Nahdlatul Ulama (NU) in Parepare with cultural propaganda approach towards religious tolerance approach hadith/sunnah of the Prophet in the city of Pare Pare. This study used a qualitative descriptive research (qualitative-descriptive research), with reference to the method through direct observation, interviews, chances focus group discussion (FGD), and through the study documentation. In analyzing the data used content analysis or content analysis, to analyze the meanings of the values and principles of cultural propaganda contained in the overall ideas and concepts in cultural propaganda NU Pare Pare.Some cultural missionary movement that has been played by NU Parepare in guarding religious harmony, as follows: (1) Investment value was sediri culture as something noble; (2) Develop a strategy of cultural propaganda through the values of local wisdom; (3) intensifed religious dialogue, both religious sesame interal and external; (4) Making Charter of Medina as a source of reference material in cultural propaganda. While the values of the Medina Charter, among others: Brotherhood (al-ikha â), equation (al-musawwah), freedom (al-hurriyyah), pluralism and diversity (pluralism), tolerance (tasamuh), and the values of taâawwun. Cultural propagation problems be an integral in maintaining and values of tradition/culture, society, so must of intensively